A multi-scale analysis of vegetation and irrigation heterogeneity effects on ecohydrological function and ecosystem services in a semi-arid urban area - Gage, Edward A., author; Cooper, David, advisor; Ham, Jay, committee member; Kampf, Stephanie, committee member; Ryan, Michael, committee member (Colorado State University. Libraries, 2014)
To view the abstract, please see the full text of the document.
Keywords: ecohydrology; urban; vegetation; water resources; ecosystem services; GIS